Development and characteristics of preclinical experimental models for the research of rare neuroendocrine bladder cancer - Höfner, Thomas; Macher-Göppinger, Stephan; Klein, Corinna; Rigo Watermeier, Teresa; Eisen, Christian; Pahernik, Sascha; Hohenfellner, Markus; Trumpp, Andreas; Sprick, Martin (The journal of urology, 2013)
Purpose: - - For rare cancers such as neuroendocrine bladder cancer treatment options are limited due partly to the lack of preclinical models. Techniques to amplify rare primary neuroendocrine bladder cancer cells could provide novel tools for the discovery of drug and diagnostic targets. We developed preclinical experimental models for neuroendocrine bladder cancer. - - Materials and Methods: - - Fresh tumor tissue from 2 patients with neuroendocrine bladder cancer was used to establish in vitro and in vivo models. We analyzed additional archived tissues in the National Center of Tumor Diseases tissue bank from patients with neuroendocrine bladder cancer. Primary tumor samples were collected during radical cystectomy. PHA-665752 was used to inhibit MET in animal models and cell cultures. The expression of markers and drug targets in neuroendocrine bladder cancer was determined by flow cytometry. The growth of neuroendocrine bladder cancer in vitro was determined by counting live cells. Tumor growth in mice was assessed by measuring tumor volume. Groups were compared using the nonparametric Kruskal-Wallis test. - - Results: - - Xenograft models and serum-free cultures of neuroendocrine bladder cancer cells allowed screening for cell surface markers and drug targets. We found expression of the HGF receptor MET in neuroendocrine bladder cancer cultures, xenograft models and primary patient sections. The growth of neuroendocrine bladder cancer spheroids in vitro depended critically on HGF. Treatment of neuroendocrine bladder cancer bearing mice with a MET inhibitor significantly decreased tumor growth compared to that in control treated mice. - - Conclusions: - - Neuroendocrine bladder cancer xenografts and serum-free cultures provided suitable models in which to identify diagnostic markers and therapeutic targets. Using the models, we noted HGF dependent growth of human neuroendocrine bladder cancer and identified MET as a new treatment target for neuroendocrine bladder cancer.
Gesehen am 13.07.2021